DEVELOPING A FRAMEWORK FOR SUPPLY CHAIN MANAGEMENT DISRUPTIONS IN INDIA AUTOMOBILE INDUSTRY - Ferreira De Souza, Samuel John (Digital Repository of Theses, 2023)
The study´s overall objective is to analyze what strategies organizations use to succeed in supply chain production during the pandemic and what type of analysis they have made to adjust their corporate decisions in post-pandemic. The target recipients are stakeholders in India, involved in the global supply chain, such as ports, warehouses, retailers, and organizations that needed to be aware of constant changes because of disruptions. This research aims to use qualitative descriptive research to analyze data on managerial decision processes, especially on customer satisfaction and its impact on supply chain disruptions in Indian organizations. The research seeks to answer the extent to which post-pandemic actions are needed to maintain holistic supply-chains and how will an organization's strategies assist in overcoming supply-chain disruptions. The research will also analyze the business perspective for the strategic direction and strategic profile of a company. Hence, this research seeks to demonstrate that holistic managerial decisions taken on a transformational framework of very structured criteria and assessment methods can help small and medium-size organizations to use levers of business excellence and innovation to improve in a world of competitiveness and performance. The research implications are to help firms and supply chain managers to rediscover their potential and capacity to achieve innovation and business excellence by using performance levers.